Factors influencing nursing students’ decisions to specialize in mental health: The role of educational, professional, and personal experiences - Pim Cuijpers; Marit M van Buuren; Koen Nieman (Malahayati International Journal of Nursing and Health Science, 2026)
Background: A significant global shortage of mental health nurses exists. Additionally, compared to other nursing specialities, mental health nursing has been determined to be less popular at University Medical Center Utrecht of Applied Sciences. Purpose: a better understanding of what influences second-year nursing students' choice to minor in mental health. Method: Survey-based quantitative methodology was used. The sample consisted of 177 second-year nursing students pursuing bachelor's degrees. Results: Multiple linear regression revealed that four factors—students' interest in mental health care, teachers' knowledge of the topic, previous internships in mental health care, and the experience of a close relative with mental health concerns—were significantly connected with the decision to minor in mental health. Conclusion: The findings indicate that choosing a child or adolescent with mental health issues as a focus of care is relatively uncommon. Moreover, the decision to work with this population was not associated with all themes identified in previous qualitative studies. Several variables were excluded from the analysis due to limited conceptual clarity or insufficient understanding. Overall, the observed effect sizes were modest.